Polymer composites for obtaining human anatomic structures - Oleksy, Małgorzata; Dynarowicz, Klaudia; Aebisher, David (Polimery, 2023)
Composites based on PLA with the addition of 3, 6 and 10 wt% silica, hydroxyapatite and bentonite were obtained by twin-screw extrusion. Maleic anhydride grafted polyethylene was used to enhance interface interactions. The influence of the fillers used on the Charpy impact strength, Rockwell hardness, tensile properties and processing shrinkage was investigated. Test samples were obtained by 3D printing. The highest impact strength and hardness were obtained for the composite containing 10 wt% hydroxyapatite. PLA with 10 wt% hydroxyapatite and 3 wt% bentonite was used to obtain anatomical structures by 3D printing.